ANALYSIS OF THE IMPACT OF USE OF SUPER COIL G COIL AND CPR9EAIX-9B COIL ON THE PERFORMANCE OF ENGINE MOTORCYCLE TYPE 2PV (xxxx-xxxx, 2024)
The rapid development of automotive technology is driving innovation in motor vehicle ignition systems, especially on combustion motors in the Otto motor type. (gasholine). One of the major problems faced is the underoptimal performance of standard ignition systems, which affects power, torque, fuel consumption, and exhaust gas emissions. The research is aimed at addressing the problem by testing the impact of replacing standard lighting system components with alternative spare parts products on motorcycles with 2PV engine code. The research method used is experimental replacement of standard coils with Super Coil G coils and standard hose with CPR9EAIX-9B hose. Tests are carried out to measure torque, power, fuel consumption, and exhaust gas emissions before and after modification using Shell Super 92 fuel. Based on laboratory test results, the highest torque was achieved by the Super Coil G variation and the CPR9EAIX-9B foam variation of 18.1 N.m. The highest power was obtained by the standard G super coil variation with 20.35 HP. The lowest fuel consumption was reached by a standard G Super coil variant and a standard foam variant of 0.12 liters per hour. The results of empirical testing showed that variations of standard coils and standard hose resulted in a maximum speed of 102 km/h. The research provides an impact of practical solutions to improve motorcycle performance and support efforts to reduce exhaust gas emissions, in accordance with the standard quality standards of exhaustive gases set by the government.